Peran Pancasila dalam Membangun Keharmonisan Sosial di Era Globalisasi - Permata, Divia Atma (Maliki Interdisciplinary Journal, 2024)
Pancasila, as the foundational ideology of Indonesia, plays a pivotal role in fostering social harmony within the country's diverse cultural, religious, and ethnic landscape. In the context of globalization, which introduces rapid social and cultural transformations, Pancasila serves as a relevant moral compass that underpins unity, justice, and solidarity among Indonesian society. This article explores the core values embedded in each of the five principles of Pancasila and their significance in promoting harmonious social relations. The principles of Pancasila emphasize respect for diversity, social justice, and national unity, which are essential in addressing the challenges posed by globalization, such as cultural homogenization, social polarization, and the erosion of local identities. As foreign cultures and technological advancements continue to shape Indonesian society, Pancasila remains a guiding force that helps balance modernization with the preservation of traditional values. Furthermore, the article discusses the challenges in instilling Pancasila’s values among the younger generation and the growing influence of global culture through digital media. To address these issues, the article suggests strengthening Pancasila education, reinforcing the role of social institutions such as families, schools, and communities, and fostering collaboration between the government and society. When implemented effectively, Pancasila will continue to serve as a critical foundation for maintaining social harmony, promoting inclusivity, and safeguarding the nation’s cultural identity amid the globalized world.